Pengaruh viral marketing dalam dimensi messenger, message dan environment terhadap keputusan pembelian - Agnes Fiorentina (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2018)
The purpose of this research is to understand the influence viral marketing in dimensions messenger, message and environtment towards purchase decision of Miting Lobster. This research is a quantitative research by using the SPSS Statistic 20 with 191 respondent of sample which is consumer Miting Lobster in DKI Jakarta and Bekasi who have bought prducts Miting Lobster three times or more using non-probability sampling method. The result of this research show that psychological factors significantly influence the purchase decision with the coefficient of regression is 0,611. The implications of this research can be a reference for the management team in formulating Miting Lobster sales strategy related to viral marketing in the discussion of messenger, message, environtment and purchase decision